Validation, Adaptation and Assessment of Orofacial Esthetic Scale in Hindi Language - Paulina; Pankaj Dhawan; Neha Jain; Uswah Khan (Indian Journal of Dental Research)
Context: The Hindi version of the Orofacial Esthetic Scale (OES) captures esthetic preferences and concerns specific to Hindi-speaking populations, making it more accessible to a wider audience. It also facilitates clear communication between healthcare professionals and patients, enhancing understanding and interactions. It facilitates cross-cultural research and helps improve healthcare equity by ensuring quality healthcare services tailored to the needs of the population. Aims: The aim of the study was to adapt and assess the Hindi version of the Orofacial Esthetic Scale-Hindi version (OES-H), validated for subjects needing or not needing prosthodontic treatment. Settings and Design: The study was conducted in the prosthodontic department of the institution. Patient recruitment was carried out consecutively until the required test population size of 162 patients was achieved. Patients were categorized into three groups based on their treatment requirements: No treatment (NT) requiring group, prosthodontic treatment (PT) requiring group, and esthetic prosthodontic treatment (EPT) requiring group. Patient recruitment for the NT group occurred during routine hygiene check-ups, while recruitment for the PT and EPT groups took place at the commencement of PT. Methods and Materials: The OES-H was obtained through a cross-culture adaptation process. The psychometric properties of the obtained version were then observed in a group of 54 prosthodontic and 54 non-prosthodontic patients and 54 patients requiring EPT. Statistical Analysis Used: Discriminant and convergent validity and reliability were measured. Results: The OES-H scores were found to be significantly higher for subjects not requiring EPT. Conclusions: The OES-H can be used as an effective tool for measuring the self-perceived aesthetic appearance in dental practice and research.